Bagon Village Waste Management Innovation Through Optimizing the Role of the Waste Bank - Nur Andita Prasetyo; Suhesti Yulfiani; Mayang Luthfiah Noviana; Ewin Eka Sofia Wulandari; Ahmad Nawawi (RECORD: Journal of Loyality and Community Development, 2024)
Waste management is still a complex matter, and of these problems there are many program innovations to deal with waste management problems. The program innovation for dealing with waste came from KKN-K students in group 023 who designed work programs that were in line with environmental problems in Bagon Village, namely the lack of handling of waste problems. The lack of waste handling in Bagon Village is proven through the results of a survey directly to the community. The survey results found that most of the people of Bagon Village still littered. The "Waste Bank" work program is a form of work program in the environmental field which will later be realized by the KKN-Collaboration group 023. KKN activities require students to be able to solve problems that occur in society, both from natural resources and human resources, assisting the development of a place to be more advanced than before, 023 Collaborative Community Service Students conducted Community Service Program to empower the Bagon Village Community based on waste bank management